Glyphosate-Resistant Palmer Amaranth Control in XtendFlex Soybean - R. Liu; V. Kumar; T. L. Lambert (Kansas Agricultural Experiment Station Research Reports, 2022)
XtendFlex soybean is a triple-stacked trait technology that allows growers to use dicamba (XtendiMax) and glufosinate (Liberty) for in-season control of glyphosate-resistant (GR) weed species, including Palmer amaranth. A field study was conducted at the Kansas State University Agricultural Research Center (KSU-ARCH) near Hays, KS, to determine the effectiveness of POST applied XtendiMax and Liberty alone or in sequential applications for GR Palmer amaranth control in XtendFlex soybean. The study site had a natural infestation of GR Palmer amaranth. Results showed that early post-emergence (EPOST) applications of XtendiMax or Liberty followed by (fb) a late post-emergence (LPOST) application of Liberty provided an excellent control (98%) of GR Palmer amaranth compared to XtendiMax or Liberty alone at 30 days after treatment (DAT). All treatments provided>80% control throughout the season, except for Roundup PowerMax alone (59 to 78%). Consistent with percent visual control, all tested treatments significantly reduced GR Palmer amaranth biomass (0 to 96 g/10 ft2) compared to non-treated check (178 g/10 ft2). Soybean yield for majority of the tested treatments were significantly higher (ranging from 28 to 33 bu/a), compared to nontreated check (23 bu/a). In conclusion, these results suggest that sequential treatments of EPOST XtendiMaxfbLPOST XtendiMax or Liberty and EPOST LibertyfbLPOST Liberty can provide effective control of GR Palmer amaranth in XtendFlex soybeans.
Keywords: Glyphosate-resistant; management; Palmer amaranth; XtendFlex soybean